A60 SIGNIFICANCE OF IBD DIAGNOSIS IN THE BC COLON SCREENING PROGRAM. (4th March 2021) - Bedi, H K; Telford, J J; Schaeffer, D; Penner, R M; Atkinson, K; Fu, Y; Wiesinger, H; Rioux, K P; Salh, B
Abstract: Background: There has been evidence of incidental inflammatory bowel disease (IBD) diagnosis in otherwise asymptomatic patients during colonoscopy to follow-up a positive fecal immunochemical test (FIT). Little is known about the significance of subclinical disease and its progression in this population. Aims: To determine the incidence and outcome of subclinical IBD in a colon screening program. We hypothesize that the proportion of patients receiving biologic or surgical intervention would be low. Methods: IBD cases were identified using the BC Colon Screening Program (BCCSP) database; pilot program at 3 sites from 01/2009–11/2013, and province-wide from 11/2013- 12/2017. Inclusion criteria: diagnosis of IBD at BCCSP colonoscopy performed for positive FIT. Exclusion criteria: prior IBD diagnosis, microscopic colitis. Data obtained through chart review included: demographics, endoscopy and histology reports, and medical/surgical treatment. Results: Of 93, 994 colonoscopies, 608 were diagnosed with IBD (0.65%) (Figure 1). Chart review of 245 cases at 10 institutions was performed. 65 patients were excluded. Of the 180 cases included, the average age at diagnosis was 59.6 years and 58.9% were male. 70.6% of patients were Caucasian, 12.2% were East Asian, and 7.8% South-east Asian. 49.4% were diagnosed with Crohn's disease (CD), 33.9% with Ulcerative Colitis (UC), and 16.7% with indeterminate colitis, with a median follow-up of 25.5 months (0–85.9 months). 62.8% of patients received treatment, with 17.8% requiring biologic therapy, and 1.7% requiring surgical intervention. Conclusions: This is the largest study assessing subclinical IBD in a colon screening program, with IBD incidence comparable to other publications in this population. However, the high proportion of patients diagnosed with CD is a novel finding. Also, subclinical IBD is not as benign as previously reported as nearly 20% of patients required biologics and/or surgical intervention. Funding Agencies: None